Hepatitis B and C virus infection among healthcare workers in Africa: a systematic review and meta-analysis - Daniel Atlaw; Biniyam Sahiledengle; Zerihun Tariku (Komiyama Printing Co. Ltd, 2021)
Abstract Background Healthcare workers are at risk of acquiring hepatitis B and C virus infections through patients' blood and bodily fluids exposure. So far, there is no pooled data that shows the prevalence of HBV and HCV among health care workers in Africa. This study aimed to determine the pooled prevalence of hepatitis B and C infections among health care workers in Africa. Methods Studies reporting the prevalence of HBV and HCV were identified from major databases and gray literature. PubMed, CINAHL, POPLINE, ScienceDirect, African Journals Online (AJOL), and Google Scholar were systematically searched to identify relevant studies. A random-effect model was used to estimate the pooled prevalence of hepatitis B and C among health care workers in Africa. The heterogeneity of studies was assessed using Cochran Q statistics and I2 tests. Publication bias was assessed using Begg's tests. Result In total, 1885 articles were retrieved, and 44 studies met the inclusion criteria and included in the final analysis. A total of 17,510 healthcare workers were included. The pooled prevalence of hepatitis B virus infection among health care workers in Africa is estimated to be 6.81% (95% CI 5.67-7.95) with a significant level of heterogeneity (I2 = 91.6%; p < 0.001). While the pooled prevalence of hepatitis C virus infection using the random-effects model was 5.58% (95% CI 3.55-7.61) with a significant level of heterogeneity (I2 = 95.1%; p < 0.001). Conclusion Overall, one in fifteen and more than one in twenty healthcare workers were infected by HBV and HCV, respectively. The high burden of HBV and HCV infections remains a significant problem among healthcare workers in Africa.